2021
DOI: 10.9770/jesi.2021.9.2(26)
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization and human capital development

Abstract: The onset of Fourth Industrial Revolution and its related development of digitization processes has created the need to focus more attention on creating the conditions for the development of adequate human resources skills, on which the pace of innovation depends. The digital transformation of economies has become a global trend, so the need to innovate cannot be ignored if countries want to be competitive in international environment. Therefore, particular governments must respond to this situation and take r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Between 2010 and 2019, there were changes in education in Slovakia due to the onset of the fourth industrial revolution. At that time, the number of university graduates began to increase, from 15.1% to 23.1% [10]. Bolek et al (2021) [116] state that in most cases (almost 70% of them) managers in Slovakia have a second-level university education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2010 and 2019, there were changes in education in Slovakia due to the onset of the fourth industrial revolution. At that time, the number of university graduates began to increase, from 15.1% to 23.1% [10]. Bolek et al (2021) [116] state that in most cases (almost 70% of them) managers in Slovakia have a second-level university education.…”
Section: Discussionmentioning
confidence: 99%
“…It would contribute to the expansion of knowledge in the field of HCM and digitalization. Moreover, it would follow on from studies such as digitalization and development of HC in EU countries [10], HC during digital transformation in Ukraine [11], the impact of digitalization on HC in Russia [12], use of HC in the digital economy in Russia [13].…”
Section: Introductionmentioning
confidence: 99%
“…The crisis generated by COVID-19 has created some major problems, which have significantly accelerated the use of digital tools, which have highlighted on the one hand the opportunities and facilities that are offered through them, but on the other hand, digital inequalities have also been highlighted (Androniceanu et al, 2022;Ivanová et al,2021;Androniceanu and Marton, 2021). In our research, they are identified and analyzed on each component.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, younger employees are more inclined to adopt and adjust to modern technological skills or join firms with higher innovation potential. Likewise, Ivanová et al (2021) discussed the need for continuous skill development and education to ensure that workers can adapt to the changing demands of the digital age. They emphasise the importance of developing digital literacy and thinking critically, solving complex problems, and working collaboratively in the digital environment.…”
Section: Introductionmentioning
confidence: 99%